Additive-free, selective synthesis of N-heteroaromatics using morphology-engineered hollow CeO2 nanocatalyst - Singh, Nittan; Swapna, Bhattu; Balu, Alina Mariana; Bhatte, Kushal; Sudarsanam, Putla (ACS Sustainable Chemistry & Engineering, 2025)
We developed a highly efficient, shape-controlled CeO2 nanocatalyst for synthesizing N-heteroaromatics via an aerobic dehydrogenation approach, operating at mild reaction conditions without needing toxic acid/base additives. Different morphologies of CeO2, namely, hollow nanospheres, nanorods, and irregularly shaped nanoparticles, were synthesized, as confirmed by electron microscopy analysis. The CeO2 hollow nanosphere catalyst (CeO2-HNS) exhibited unique features, such as abundant acid-base sites, larger-sized voids, and surface oxygen vacancies. These characteristics are found to be crucial for the additive-free oxidative dehydrogenation of saturated N-heterocycles over the CeO2-HNS catalyst, resulting in 98% conversion of 1,2,3,4-tetrahydroquinoline with 100% quinoline product selectivity. The versatility of this approach was further demonstrated by the successful aerobic dehydrogenation of a broad range of saturated N-heterocycles, affording N-heteroaromatics in good to excellent yields. Furthermore, the CeO2-HNS nanocatalyst showed exceptional reusability over six cycles without requiring a regeneration step, such as high-temperature calcination treatment. The structural and morphological stability of the CeO2-HNS catalyst, along with reaction scalability and favorable green chemistry metrics, emphasized the practical viability of the CeO2-HNS catalyst for industrial applications.
Keywords: acid-base and defect sites; additive-free aerobicdehydrogenation; CeO2 hollow nanosphere catalyst; N-heteroaromatics; reusability and scalability